Diabetic Foot Ulcers: Insights into Management and Prevention - Muhammad Kashif Rafiq, Haider Kamran, Asif Ayub, Fouzia Jameel, (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetic foot ulcer (DFU) is one of the greatest thoughtful difficulties of diabetes, negatively affecting the patient's health and socioeconomic status. Around the world, diabetes prevalence is increasing in both developing and developed countries. There are several measures in place in most countries to limit diabetes complications. This review summarizes the pathogenic mechanisms that lead to diabetic foot and focuses on prevention and management. It may be possible to prevent diabetic foot ulcers and thus amputation risk by increasing physicians' awareness and ability to identify risky feet. Diabetes neuropathy, peripheral artery disease, and immune dysfunction are the three major contributing factors. In order to treat diabetic foot disease, a detailed history and physical examination are necessary. Diabetic neuropathy and peripheral arterial disease manifestations, such as diabetic foot ulcers and infections, should be examined during this examination. Prevention approaches should integrate a multidisciplinary method centered on patient education. Preventive efforts must, however, be sustained for a long time for them to be effective. Keywords: Diabetic foot; Ulceration; Neuropathy; Pathogenesis; Peripheral arterial disease